This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Sir, I used ln ( n + 1 n ) = ln ( 1 − n + 1 1 ) and then the series expansion, but somehow I am not able to reach the answer. Can you help me out?
Log in to reply
That will work too. In this case the limit will be
n → ∞ lim ( n + n 2 ln ( 1 − n + 1 1 ) ) .
Then using x = − n + 1 1 in the series expansion the limit becomes
n → ∞ lim ( n − n 2 ( n + 1 1 + 2 ( n + 1 ) 2 1 + 3 ( n + 1 ) 2 1 + . . . ) ) =
n → ∞ lim ( n − n + 1 n 2 − 2 ( n + 1 ) 2 n 2 − 3 ( n + 1 ) 3 n 2 + . . . . ) =
n → ∞ lim ( n + 1 n − 2 ( 1 + n 1 ) 2 1 − 3 n ( 1 + n 1 ) 3 1 − . . . . ) = 1 − 2 1 = 2 1 .
Replacing n by x 1 and further simplifying the expression, we get
lim x → 0 [ x 1 − x 2 l n ( x + 1 ) ]
Now expanding,we get
x 1 − x 2 1 [ x − 2 x 2 + 3 x 3 − . . . . . . . . . . . . . ]
A n s . 2 1
The simpliest computation for limit n → ∞ lim ln [ e n ( n + 1 n ) n 2 ] = u → e lim ( ln ( u ) ) Apply the chain rule: if u → b lim ( f ( u ) ) = L a n d u → a lim ( g ( x ) ) = b a n d f ( x ) is continuous at x = b . T h e n : x → a lim ( f ( g ( x ) ) ) = L = ln ( e ) = 2 1 □
FIN!!!
Problem Loading...
Note Loading...
Set Loading...
This limit can be written as
n → ∞ lim ( ln ( e n ) + ln ( n + 1 n ) n 2 ) = n → ∞ lim ( n + n 2 ln ( n + 1 n ) ) =
n → ∞ lim ( n − n 2 ln ( n n + 1 ) ) = n → ∞ lim ( n − n 2 ln ( 1 + n 1 ) ) .
Now the Maclaurin series for ln ( 1 + x ) is
ln ( 1 + x ) = x − 2 x 2 + 3 x 3 − 4 x 4 + . . . for − 1 < x ≤ 1 .
So with x = n 1 our limit becomes
n → ∞ lim ( n − n 2 ( n 1 − 2 n 2 1 + 3 n 3 1 − 4 n 4 1 + . . . ) ) = n → ∞ lim ( n − n + 2 1 − 3 n 1 + 4 n 2 1 − . . . . ) =
n → ∞ lim ( 2 1 + O ( n 1 ) ) = 2 1 = 0 . 5 .